(untitled) (Global Journal of Medical Research, 2013)
Background: Inguinal hernia is common surgical problem in paediatrics and incarceration is the most common subsequent complication if left untreated. The fact that there is effect of the socioeconomic factors on development of incarceration in form of delayed presentation. Objectives: To determine the relation between socioeconomic status and development of incarcerated inguinal hernia among children presented to (GNCPS). Results: 43 case presented with incarcerated inguinal hernia within the study period those